Electromyographic patterns of lower limb muscles during apprehensive gait in younger and older female adults - Hallal, Camilla Zamfolini [UNESP]; Marques, Nise Ribeiro [UNESP]; Spinoso, Deborah Hebling [UNESP]; Vieira, Edgar Ramos; Gonçalves, Mauro [UNESP] (Elsevier, 2013)
Objective: Investigate the influence of apprehensive gait on activation and cocontraction of lower limb muscles of younger and older female adults. Methods: Data of 17 younger (21.47±2.06 yr) and 18 older women (65.33±3.14. yr) were considered for this study. Participants walked on the treadmill at two different conditions: normal gait and apprehensive gait. The surface electromyographic signals (EMG) were recorded during both conditions on: rectus femoris (RF), vastus lateralis (VL), vastus medialis (VM), biceps femoris (BF), tibialis anterior (TA), gastrocnemius lateralis (GL), and soleus (SO). Results: Apprehensive gait promoted greater activation of thigh muscles than normal gait (F=5.34 and p=0.007, for significant main effect of condition; RF, p=0.002; VM, p<0.001; VL, p=0.003; and BF, p=0.001). Older adults had greater cocontraction of knee and ankle stabilizer muscles than younger women (F=4.05 and p=0.019, for significant main effect of groups; VM/BF, p=0.010; TA/GL, p=0.007; and TA/SO, p=0.002). Conclusion: Apprehensive gait promoted greater activation of thigh muscles and older adults had greater cocontraction of knee and ankle stabilizer muscles. Thus, apprehensive gait may leads to increased percentage of neuromuscular capacity, which is associated with greater cocontraction and contribute to the onset of fatigue and increased risk of falling in older people. © 2013 Elsevier Ltd.
Keywords: Biomechanics; Cocontraction; Dual task gait; Elderly; Falls; adult; aged; biceps brachii muscle; biomechanics; electromyogram; falling; female; gait; gastrocnemius muscle; human; leg muscle; muscle contraction; priority journal; rectus femoris muscle; soleus muscle; task performance; tibialis anterior muscle; treadmill exercise; vastus lateralis muscle; vastus medialis muscle; walking speed